PENGEMBANGAN PRAKTIKUM SAINS BERBASIS KEUNGGULAN LOKAL MELALUI PEMBUATAN PRODUK PANGAN RUMPUT LAUT - Karepesina, Nur Gaib; Habiddin, Habiddin (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Environmental based learning aims to improve students' cognitive abilities and skills. Local excellence-based on science practicums are able to apply their knowledge, to find ideas, and implement it to motivate students to study hard. Where the learning resources concrete and more contextual through the manufacture of seaweed food products starting from analysis, design, development, and implementation (sampling and preparation, sample processing, product assessment) have resulted in a deep student understanding of the material. Students have creative abilities (14.8%), taste (13.5%), aroma (13.8%), appearance (14.5%), texture (13.5%), nutritional diversity (14.2%), and hygiene (15.7%), with an average level of understanding and skill of students in each group of 88.3%. Based on the practicum of making seaweed food products, students will become more creative, innovative, skilled, and improve their cognitive abilities.